2015
DOI: 10.1681/asn.2015070796
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide Attenuates Lithium–Induced Nephrogenic Diabetes Insipidus

Abstract: To reduce lithium-induced nephrogenic diabetes insipidus (lithium-NDI), patients with bipolar disorder are treated with thiazide and amiloride, which are thought to induce antidiuresis by a compensatory increase in prourine uptake in proximal tubules. However, thiazides induced antidiuresis and alkalinized the urine in lithium-NDI mice lacking the sodium-chloride cotransporter, suggesting that inhibition of carbonic anhydrases (CAs) confers the beneficial thiazide effect. Therefore, we tested the effect of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
28
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 72 publications
0
28
1
Order By: Relevance
“…These side effects were not observed in the acetazolamide-treated mice with lithium-induced NDI. de Groot et al 3 also found that acetazolamide treatment of mice with lithium-induced NDI reduces inulin clearance, reduces the cortical expression of the sodium/hydrogen exchanger 3, and reduces the increase in urinary prostaglandin E 2 observed in mice with lithium-induced NDI.…”
mentioning
confidence: 93%
See 3 more Smart Citations
“…These side effects were not observed in the acetazolamide-treated mice with lithium-induced NDI. de Groot et al 3 also found that acetazolamide treatment of mice with lithium-induced NDI reduces inulin clearance, reduces the cortical expression of the sodium/hydrogen exchanger 3, and reduces the increase in urinary prostaglandin E 2 observed in mice with lithium-induced NDI.…”
mentioning
confidence: 93%
“…de Groot et al 3 found that, in mice with lithium-induced NDI, treatment with either acetazolamide or thiazide/amiloride resulted in a similar reduction of polyuria, increase in urine osmolality, and increase in AQP2 protein abundance. However, the side effects of the two treatment regimens were different.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…2 Acetazolamide monotherapy was as effective as the combination of hydrochlorothiazide and amiloride in reducing polyuria in an animal model of lithium-induced nephrogenic diabetes insipidus but had fewer side effects. 3 Acetazolamide reduces the glomerular filtration rate by means of tubuloglomerular feedback and reduces renal prostaglandin secretion; both effects attenuate polyuria induced by nephrogenic diabetes insipidus.…”
Section: Acetazolamide In Lithium-induced Nephrogenic Diabetes Insipidusmentioning
confidence: 99%